Alexander the great - Rossen, Robert ([S.l.] : Metro-Goldwyn-Myer Studios [production company] ; Kuala Lumpur : Movie Magic [distributor], 1999)
The story of Alexander the Great, Greek hero and world-conqueror, is given epic treatment as international stars Richard Burton, Fredric March and Claire Bloom join a cast of thousands to bring history to life
n.2 and n.3 is acquisition for KPI (Kelab Pencinta Ilmu)
Richard Burton, Fredric Marc, Claire Bloom
Keywords: Alexander, -- the Great, -- 356-323 B.C -- Military leadership; Generals -- Macedonia -- Biography; Greece -- History -- Macedonian Expansion, B.C.